The discourse of argumentation in the Malaysian commercial work context - Manjit Kaur (Journal of Modern Languages)
This paper seeks to impart observations on how personnel at the Malaysian workplace utilised discourse strategies and gave opinions, agreed, disagreed, proposed, reached outcomes and performed other speech functions associtated with argumentation and negotiation. The study draws on explicit knowledge of how people use discourse strategies for argumentation and negotiation in that domain so that we can bring this knowledge back to the classroom to help prep.are tertiary students. This is to help empower students in order that they can participate effectively in work exchanges on entering the workforce.